Samband mellan Brottsutsatthet och Individers Egenskaper - En analys baserad på NTU-data - Ma,Louise; Astrén,Jenny (2024)
While the Swedish debate on crime often centers around crime, punishment, and offenders, there is notably less attention dedicated to those who are exposed to crime. This discrepancy is particularly evident in the lack of comprehensive theories explaining who becomes a victim. This thesis investigates whether a pattern can be identified between what kind of background or exposure of crime and being a victim to a particular type of crime. In this study, logistic regression is used to analyze a data material came from a Swedish Crime Survey conducted by The Swedish National Council for Crime Prevention annually. Out of 14 types of crimes, we studied further to three specific types: robbery, sexual offenses and assault. In conclusion, we were able to find a pattern of crime victimization vary based on different backgroundfactors. It is difficult to make general statement about gender, but younger people or being a single parent with children have a higher risk to be exposed of these crimes, also in correlation between be threaten and all crime models we studied.
Keywords: Logistic regression; Crime Prevention; Crimes.